IMF Committee on Balance of Payments Statistics : Annual Report 2009. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2010)
This Annual Report of the IMF Committee on Balance of Payments Statistics (Committee) for 2009 provides an overview of recent trends in balance of payments and international investment position statistics. The Annual Report also discusses the Committee's work program during 2009 and reviews the issues the Committee plans to address in the coming year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet